Relational Incentive Contracts - Levin, Jonathan (American Economic Review, 2003)
Standard incentive theory models provide a rich framework for studying informational problems but assume that contracts can be perfectly enforced. This paper studies the design of self-enforced relational contracts. I show that optimal contracts often can take a simple stationary form, but that self-enforcement restricts promised compensation and affects incentive provision. With hidden information, it may be optimal for an agent to supply the same inefficient effort regardless of cost conditions. With moral hazard, optimal contracts involve just two levels of compensation. This is true even if performance measures are subjective, in which case optimal contracts terminate following poor performance.